The Role of Digitalization Development for Micro, Small and Medium Enterprises (MSMEs) in Ambon City - Agoha, Rulandus Michael; Sinay, Francisca Riconita; Louhenapessy, William George M (Universitas Pattimura, 2025)
This study aims to explore the role of digitalization in the development of Micro, Small, and Medium Enterprises (MSMEs) in Ambon City, particularly MSMEs under the guidance of Bank Indonesia Maluku Province. Using a descriptive qualitative research method, data were collected through in-depth interviews and observations of three MSMEs: Ralsasam Tenun, Sumakul, and Kabeta Craft. The findings show that digitalization training and facilitation through exhibitions significantly enhanced MSMEs' capacity to utilize digital media, such as Instagram and marketplaces, for product promotion and marketing. Digitalization has proven effective in expanding market reach and increasing sales, with the three MSMEs reporting a 50% increase in revenue. The study implies that the implementation of digitalization in MSME marketing strategies can be a solution for improving competitiveness and business sustainability in the digital era